Feasibility of RME-Based Bilingual E-Module on 3D Shapes with Curved Surfaces - Pitriani Pitriani; Putra Pratama (Universitas Sarjanawiyata Tamansiswa, 2021)
A bilingual e-module that is systematically structured and linked to contextual problems can help students learn independently anywhere and anytime, especially in a pandemic that applies distance learning. RME is an approach that views mathematics as an activity/ process in contextual problems so that students find their own understanding. This study examines the feasibility of an RME-based bilingual e-module on 3D shapes with curved surfaces materials from expert judgment on material, language, and media. This research model is the ADDIE model. There are 6 validators (2 material experts, 2 media experts, and 2 linguists). The research instrument was in the form of assessment based on expert judgement. The results showed that both material, media, and language used for the RME-based bilingual e-module is